2013
DOI: 10.5468/ogs.2013.56.2.93
|View full text |Cite
|
Sign up to set email alerts
|

The ON-Q pain management system in elective gynecology oncologic surgery: Management of postoperative surgical site pain compared to intravenous patient-controlled analgesia

Abstract: ObjectiveThe goal of this study was to compare postoperative surgical site pain in gynecologic cancer patients who underwent elective extended lower midline laparotomy and managed their pain with either the ON-Q pain management system (surgical incision site pain relief system, ON-Q pump) or an intravenous patient-controlled analgesia pump (IV PCA).MethodsTwenty gynecologic cancer patients who underwent elective extended lower midline laparotomy were divided into two groups. One group received a 72-hour contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Therefore, four full-texts were considered as source of data for decision tree modeling and economic assessment regarding the control of postoperative pain related to cancer surgical treatment. [7][8][9][10] Three studies analyzed intravenous administration of postoperative analgesia, controlled by the patient, [8][9][10] and the fourth study indicated use of epidural analgesia 7 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, four full-texts were considered as source of data for decision tree modeling and economic assessment regarding the control of postoperative pain related to cancer surgical treatment. [7][8][9][10] Three studies analyzed intravenous administration of postoperative analgesia, controlled by the patient, [8][9][10] and the fourth study indicated use of epidural analgesia 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Only one study presented analgesia on demand, 9 and the other three presented continuous infusion with bolus, if necessary. 7,8,10 Two studies analyzed intensity of pain during the 48 hour period after surgery, 7,8 one study analyzed it during a period of 24 hours after surgery 9 and one study analyzed it during a period of 96 hours after surgery. 10 Each study analyzed different comparators and different combinations of medication for analgesia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ozbiljnost ovog poremećaja je u značajnoj meri povezana sa primenom opioida 4 . Iako je efikasnost subfascijalne infiltracije rane lokalnim anestetikom potvrđena u hirurgiji jetre, želuca, materice, kolorektalne hirurgije, žučnih puteva i ortopedskoj hirurgiji, ima vrlo malo podataka o njenoj upotrebi u barijatrijskoj hirurgiji 1,5,6,7,8,9,10,11 . Prikazujemo slučaj modifikovane tehnike intermitentne subfascijalne infiltracije rane kod gojazne pacijentkinje, nakon otvorenog želu-dačnog bajpasa.…”
Section: Introduction: Infiltration Of the Surgical Wound With Local unclassified